2022
DOI: 10.1126/science.abn3103
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy nanoparticles: Synthesis-structure-property relationships and data-driven discovery

Abstract: High-entropy nanoparticles have become a rapidly growing area of research in recent years. Because of their multielemental compositions and unique high-entropy mixing states (i.e., solid-solution) that can lead to tunable activity and enhanced stability, these nanoparticles have received notable attention for catalyst design and exploration. However, this strong potential is also accompanied by grand challenges originating from their vast compositional space and complex atomic structure, which hinder comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
287
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 464 publications
(289 citation statements)
references
References 115 publications
0
287
0
2
Order By: Relevance
“…[15][16][17][18] Meanwhile, their high entropy and sluggish diffusion effects greatly enhance their thermal and chemical stability and corrosion resistance, ensuring that HEAs can operate stably under harsh conditions. 19,20 For instance, Huang et al reported that PtRuNiCoFeMo HEA sub-nanometer nanowires (SNWs) with strong interactions between different metal sites exhibited good activity for the alkaline hydrogen oxidation reaction. 18 Alternatively, hollow structures further amplify the activity of catalysts due to their various advantageous properties, including fully exposed active sites, reduced path lengths for reactants, and enhanced utilization of precious metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Meanwhile, their high entropy and sluggish diffusion effects greatly enhance their thermal and chemical stability and corrosion resistance, ensuring that HEAs can operate stably under harsh conditions. 19,20 For instance, Huang et al reported that PtRuNiCoFeMo HEA sub-nanometer nanowires (SNWs) with strong interactions between different metal sites exhibited good activity for the alkaline hydrogen oxidation reaction. 18 Alternatively, hollow structures further amplify the activity of catalysts due to their various advantageous properties, including fully exposed active sites, reduced path lengths for reactants, and enhanced utilization of precious metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the crucial role of multiple intermediates adsorption over the electrocatalyst's surface/interfaces, more attention should be paid to creating multi-active sites in one catalytic material like high-entropy alloys to collaboratively optimize their interaction with different intermediates during 2e-WOR. [128][129][130][131][132][133][134] Recent years have witnessed a surge of interest in restructuring and strain engineering of nanocatalysts for electrocatalytic applications with improved activities including hydrogen evolution, oxygen reduction, and oxygen evolution, which may be extendable for 2e-WOR catalysts. [135,136] To promote mass transfer, tailoring the morphology of the catalysts with 3D hierarchically open porous architectures can effectively increase the availability of active sites and accelerate the diffusion of relevant species.…”
Section: Discussionmentioning
confidence: 99%
“…High‐entropy alloy (HEA) nanoparticles, composed of multiple elements (usually four or more) arranged in a single solid‐solution phase, have attracted increasing attention for catalysis due to their tunable catalytic properties, strong multielement synergy, and high‐entropy stabilization. [ 1–6 ] The use of multiple elements significantly broadens the compositional space and affords tunable microstructures to achieve high performance. It is reported that HEA catalysts are featured with complex atomic configurations and diverse adsorption sites, which result in a near‐continuous distribution in binding energy [ 7–9 ] that is well‐suited for multi‐step reactions having a wide range of intermediates.…”
Section: Introductionmentioning
confidence: 99%